Sensitivity Analysis of Inflow Conditions and Turbulence Models on Wind Turbine Wake Simulation Using an AD/RANS Approach (Advances in Applied Mathematics and Mechanics, 2018)
This work is devoted to performing systematic sensitivity analysis of differentturbulence models and various incoming wind conditions in predicting the wake flowbehind a horizontal-axis wind turbine represented by an actuator disc (AD). The testedturbulence models are the standard $k−є$ model and the Reynolds Stress Model (RSM).Employing each turbulence model, the wind turbine immersed in four inflow conditions,including both uniform and non-uniform ones, is numerically studied. Simulationresults are validated against Sexbierum field experimental data. Comparisonsshow that $k−є$ model is much more sensitive to the employed inflow conditions, withsimulated wake velocity and turbulence profiles strongly differ from one condition toanother; among them, a uniform TI & Length scale condition delivers the most accuratepredictions. By contrast, comparisons identify that RSM is less sensitive to theinflow condition implemented, and the results under all inflow conditions are consistentlyin fair match with the measurements; the RSM is found to be more robust for capturingwake behavior reliably when using the AD/RANS approach.